2021
DOI: 10.1002/suco.202100198
|View full text |Cite
|
Sign up to set email alerts
|

The effect of length and inclination of carbon fiber reinforced polymer laminates on shear capacity of near‐surface mounted retrofitted reinforced concrete beams

Abstract: This study undertakes a comprehensive investigation of the shear behavior of reinforced concrete (RC) beams strengthened by near surface mounted (NSM) carbon fiber reinforced polymer (CFRP) laminates. Different strengthening configurations were employed by varying the length and inclination angle of the CFRP laminates. Results indicated that NSM‐CFRP strengthening increased the load‐carrying capacity, ductility, stiffness, and toughness from 8% to 41%, 9% to 78%, 24% to 159%, and 22% to 254%, respectively. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
(91 reference statements)
1
17
0
Order By: Relevance
“…The explanation can be that initiated cracks meet a smoother surface which helps in delaying the crack propagation. [ 54 ] The main failure mechanism in studies has been reported with increasing deflections, crack widths, and debonding due to poor adhesion of CFRP strips to concrete cover. [ 32,81 ] Also, it is observed that the failure in NSM‐CFRP strengthening scheme occurs as a consequence of poor material, geometry, spacing, and placement patterns of material and grooves cut on the surface.…”
Section: Failure Mechanism Of Nsm‐cfrp Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The explanation can be that initiated cracks meet a smoother surface which helps in delaying the crack propagation. [ 54 ] The main failure mechanism in studies has been reported with increasing deflections, crack widths, and debonding due to poor adhesion of CFRP strips to concrete cover. [ 32,81 ] Also, it is observed that the failure in NSM‐CFRP strengthening scheme occurs as a consequence of poor material, geometry, spacing, and placement patterns of material and grooves cut on the surface.…”
Section: Failure Mechanism Of Nsm‐cfrp Techniquementioning
confidence: 99%
“…It is observed that inclined rods in the NSM-CFRP technique of retrofit are found to be more effective in enhancing the shear capacity of RC beams. [41,42,54] The position of the beams with different inclination angles of the CFRP laminates is shown in Figure 2. An experimental investigation on the concrete beams of size 150 Â 250 Â 1400 mm has shown improved shear behavior after application of CFRP NSM strips at the side cover with trapezoidal, parabolic, and straight profile using electric drill.…”
Section: Shear Enhancement Of Rc Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A parametric study on flexural performance and failure modes of NSM CFRP-strengthened concrete beams was performed by Haddad and Almomani. 27 The effect of length and fiber orientation of CFRP laminates on shear behavior of NSM F I G U R E 1 Typical application of NSM composites for strengthening reinforced concrete members retrofitted RC beams was investigated by Al-Zu'bi et al 28 Eljufout and Toutanji 29 investigated fatigue behavior of CFRP-NSM retrofitted RC beams. A comprehensive review on applications of NSM for RC structural members was reported by Al-Saadi et al 30 Validation case studies on performance of RC bridges strengthened by NSM composites are discussed by Lee et al, 31 and Yang, et al 32 Recently, Kamonna and Abd Al-Sada 33 presented results of an experimental study on performance of one-way RC slabs strengthened with near surface mounted bars.…”
Section: Introductionmentioning
confidence: 99%
“…A parametric study on flexural performance and failure modes of NSM CFRP‐strengthened concrete beams was performed by Haddad and Almomani 27 . The effect of length and fiber orientation of CFRP laminates on shear behavior of NSM retrofitted RC beams was investigated by Al‐Zu'bi et al 28 Eljufout and Toutanji 29 investigated fatigue behavior of CFRP‐NSM retrofitted RC beams. A comprehensive review on applications of NSM for RC structural members was reported by Al‐Saadi et al 30 …”
Section: Introductionmentioning
confidence: 99%